Customer Value and Data Mining in Segmentation Analysis - Gunandi, Ahmed; Awang, Heba; Alhawad, Eman; Shabaan, Lotfy (Jejaring Penelitian dan Pengabdian Masyarakat, 2023)
Customer Value is the accessed value that a customer has to an organization. In Business, the customer is always right. This statement gives us the impression that all customers are viewed as equal in terms of potential value. Each customer is treated differently according to how much profit they can bring to a company. We use various Data Mining techniques to determine who are these customers and how we can acquire more customers like them who can bring more profit. A loyal customer will be treated differently than a customer that rarely do business with the organization. These customers are usually given bonus gifts and special offers as a form of thanks for their loyalty thus further strengthening that bond. Companies need a way to determine which of their hundreds of thousands of customers are deserving of this attention. Customer Value Segments are used in this specific situation.